Evaluating the rational use of antidepressant in older patients: a comprehensive analysis of its association with cognitive impairment - Gil-Peinado, María; Pardo, Juan; García-Zamora, Mar; Adsuar-Meseguer, Gonzalo Miguel; Sendra-Lillo, José; Moreno, Lucrecia (Frontiers in Psychiatry, 2025)
IntroductionDementia and Major Depressive Disorder (MDD) are on the rise globally, with depression frequently observed throughout the progression of dementia, potentially accelerating cognitive decline and diminishing quality of life. This study aims to explore the interplay between cognitive impairment (CI) and depression in patients undergoing antidepressant treatment, emphasizing drug-related problems (DRPs) and the Rational Use of Medicines (RUM).Materials and MethodsOver a 6-year period, this cross-sectional study in Valencia, Spain, analyzed data from 777 patients aged over 50 concerned about their cognitive health. Cognitive status was assessed using three neuropsychological tests: Memory Impairment Screening (MIS), Verbal Semantic Fluency (VSF), and Pfeiffer’s Short Portable Mental State Questionnaire (SPMSQ). Various clinical and demographic variables associated with dementia were also evaluated.ResultsThe study identified a higher prevalence of CI among patients at risk of depression (GDS5 positive) compared to those without a depression risk. Patients with depression risk also demonstrated lower cognitive reserve, higher levels of loneliness, and increased use of antidepressants – notably tricyclic antidepressants (TCAs) – which are linked to anticholinergic burden and potential CI.ConclusionDespite their widespread use, antidepressants raise concerns regarding their efficacy and safety, particularly due to the risk of exacerbating CI. This study underscores the need for careful management of antidepressant therapy and suggests exploring alternatives such as vortioxetine, which may offer cognitive benefits. Enhanced interprofessional collaboration and regular cognitive evaluations are recommended to improve patient outcomes and ensure the rational use of antidepressants.